The System of Risk Management and its impact on the accounting information in the banking system - Paillacar Silva, Carlos Enrique (2019)
Objective: The article focuses on determining the relationship between an adequate application of the banking risk management system included in the regulations of the Superintendency of Banking, Insurance and the Pension Funds Administrators of Peru with the application of the standard rules of formulation of the accounting information in the banking system. Method: This is a correlational, transversal and application research. To test the relationship, a survey applied to experts was used since the banks did not provide direct information. The factors that affect the adequate application of risk management were also determined applying the Pearson's R correlation index. Results: It was demonstrated with an index of 96.7%, at a significance level of 95%, that the relevance of the banking risk management system contained in the banking regulation has an impact on the quality of the accounting information which impact has been measured in every case study. Conclusions: The relevance of the banking risk management system contained in the banking regulation has an impact on the quality of the accounting information in Peru’s banking system.